SISTEM KENDALI OTOMATIS PLTS DAN PLN PADA BEBAN LISTRIK DI LABORATORIUM ROBOTIKA BERBASIS IOT - Arianto, Fengki; Mardianto , Eko; Sufandi, Muhammad Ridhwan; Yuwono, Yohannes Chrysostomos Hendro (Electrical Network Systems and Sources, 2025)
The Department of Electrical Engineering has a Solar Power Plant (PLTS) in the robotics laboratory; however, its utilization is not optimal and is still highly dependent on electricity supplied by the national electricity grid, which poses risks such as unexpected power outages. This research aims to optimize the utilization of renewable energy through an Internet of Things (IoT)-based automatic control system. This system uses an Arduino Uno as the main microcontroller and an ESP32 to transmit data to the ThingSpeak platform. The PLTS serves as the main power source, while the PLN serves as a backup. The system automatically switches the power supply to PLN when the PLTS battery voltage drops below 10.8 V and switches back to the PLTS when the voltage exceeds 13.2 V. Data such as battery voltage, load voltage, current, and load power are displayed on an I2C LCD and visualized in ThingSpeak. Test results show that the system operates as designed, with sensor readings in accordance with manual measuring instruments, and the power supply switching occurs stably in just 1 second. After two days of testing, the system successfully reduced dependence on PLN and maximized the utilization of solar power to power student laptops in the robotics laboratory.